Implementing Literacy Program for Improving Reading Ability of Elementary School Students - Fitriyaningsih Fitriyaningsih (Universitas Pendidikan Indonesia (UPI), 2021)
This research is motivated by a lack of students’ understanding OF punctuation, as well as a lack of character in students in the school environment, especially in the learning process. Thus, a program that can improve reading skills in MI Assuniyah 03 Losari-Lor was needed through the implementation of a literacy program. The purpose of this study is to determine the implementation of literacy program, the results of literacy programs and supporting and inhibiting factors for the implementation of literacy programs in improving reading skills of third grade students at MI Assuniyah 03 Losari-Lor. This research is a qualitative research with descriptive method. Data collection techniques used were interview, observation, and documentation techniques. The ensure validity of this research data, source triangulation, triangulation technique and extended observation triangulation were used. Meanwhile the results of the research data were analyzed using data collection, data reduction, data display and withdrawal/conclusion. The results obtained in this study showed that literacy program was very important for students in MI Assuniyah 03 Losari-lor in improving reading skills. The literacy activities included: (1) silent reading, guided reading, independent reading and reading together (2) There were efforts to create facilities and a rich literacy environment with reading areas, libraries, reading corners in each class, 15 minutes reading before entering class (3) Obstacles in the implementation of literacy programs were related to time and attitudes of students.